Hair restoration surgery: challenges and solutions - Rose PT (Dove Medical Press, 2015)
Paul T RoseHair Transplant Institute of Miami, Coral Gables, FL, USA Abstract: Hair loss is a common problem affecting both men and women. The most frequent etiology is androgenetic alopecia, but other causes of hair loss such as trauma, various dermatologic diseases, and systemic diseases can cause alopecia. The loss of hair can have profound effects on one’s self esteem and emotional well-being, as one’s appearance plays a role in the work place and interpersonal relationships. It is therefore not surprising that means to remedy hair loss are widely sought. Hair transplant surgery has become increasingly popular, and the results that we are able to create today are quite remarkable, providing a natural appearance when the procedure is performed well. In spite of this, hair transplant surgery is not perfect. It is not perfect because the hair transplant surgeon is still faced with challenges that prevent the achievement of optimal results. Some of these challenges include a limit to donor hair availability, hair survival, and ways to conceal any evidence of a surgical procedure having taken place. This article examines some of the most important challenges facing hair restoration surgery today and possible solutions to these challenges. Keywords: hair loss, alopecia, hair transplant, surgical procedure